1991
DOI: 10.1111/j.1439-0442.1991.tb01045.x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Morphology and Fertility in A. I. Bulls

Abstract: Summary Furty‐seven A. I. bulls between 15 and 26 months of age, were used to study the relationship between sperm morphology in fresh semen and fertility (56‐day non‐return rate) in frozen semen following 11,749 inseminations. The sperm morphology was studied in two freezing operations/bull in a phase‐contrast microscope and morphological abnormalities were recorded as a percentage of the total number of counted spermatozoa. Morphological categories used in this study were abnormal heads, detached heads, nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1
5

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 8 publications
5
47
1
5
Order By: Relevance
“…Our results showed that SC18 genetic correlation estimates were moderate and positive with satisfactory andrological evaluation and negative with sperm defects (Table 4). These indicate that selecting for SC18 will result in ejaculates with better semen quality, as a consequence of a decreased proportion of sperm defects (Söderquist et al, 1991;Fitzpatrick et al, 2002;Al-Makhzoomi et al, 2008), in addition to a larger number of young bulls rated as satisfactory in the andrological evaluation. Within this context, the use of biométrie testicular traits and SC18 as a selection criterion may promote favorable correlated responses, including an increase in TV, semen quality, and satisfactory breeding soundness 'SC18 = scrotal circumference at 18 mo; SCAND = scrotal circumference obtained during andrological assessment.…”
Section: Resultsmentioning
confidence: 92%
“…Our results showed that SC18 genetic correlation estimates were moderate and positive with satisfactory andrological evaluation and negative with sperm defects (Table 4). These indicate that selecting for SC18 will result in ejaculates with better semen quality, as a consequence of a decreased proportion of sperm defects (Söderquist et al, 1991;Fitzpatrick et al, 2002;Al-Makhzoomi et al, 2008), in addition to a larger number of young bulls rated as satisfactory in the andrological evaluation. Within this context, the use of biométrie testicular traits and SC18 as a selection criterion may promote favorable correlated responses, including an increase in TV, semen quality, and satisfactory breeding soundness 'SC18 = scrotal circumference at 18 mo; SCAND = scrotal circumference obtained during andrological assessment.…”
Section: Resultsmentioning
confidence: 92%
“…And in a recent study, objective differences in the percentages of total and progressive motility, as well as in the velocity and straightness of spermatozoa, were found in semen from Belgian Blue and Holstein bulls (Hoflack et al, 2007). The authors suggested that a genetic component could be the basis for the breed differences in sperm motility, probably as a result of the world-wide long-term selection of highly fertile Holstein AI bulls (Söderquist et al, 1991). Although in the present study the frequency distribution of spermatozoa within subpopulations was very consistent among bulls and ejaculates, it is likely that different subpopulations could be defined when using bulls of different breeds.…”
Section: Discussionmentioning
confidence: 98%
“…Boar prolificacy depends on the quality of generated reproductive cells which can be determined by examining sperm morphology. The results of such an examination make it possible to check if a male is fertile or not (Soderquist et al 1991, Casey et al 1997, De Vos et al 2003, Philips et al 2004. A high frequency of spermatozoa with morphological abnormalities is an important indicator Correspondence to: S. Kondracki, e-mail: sk@uph.edu.pl, tel.…”
Section: Introductionmentioning
confidence: 99%